ANALISIS SISTEMATIS PENGOLAHAN SAMPAH PLASTIK LAUT DAN IMPLIKASINYA BAGI EKOSISTEM LAUT - Syamsurya, Marwah; Burhanuddin, Agussalim (Cahaya Ilmu Bangsa, 2024)
Indonesia has 187.2 million tonnes of marine plastic waste, the second largest in the world after China. Coastal areas are where land and ocean meet, and the two influence each other physically, socially and economically. Rubbish that accumulates along the coast is one of the problems that is less noticed by the community. This study uses secondary data observation research methodology from all literature, including journals, articles and scientific papers. The legal basis of waste management at the local government level, including the responsibilities imposed on the community, is controlled by Government Regulation No. 81 of 2012 concerning Management of Household Waste and Waste Similar to Household Waste, Regional Head Regulations on policies and strategies for managing household waste and waste similar to household waste, and Presidential Instruction No. 97 of 2017 concerning strategic policies for managing this type of waste. Indonesia memiliki 187,2 juta ton sampah plastik di laut terbesar kedua di dunia setelah Cina. Wilayah pesisir merupakan tempat bertemunya daratan, lautan, dan keduanya saling mempengaruhi dari segi fisik, sosial, maupun ekonomi. Sampah yang menumpuk di sepanjang pantai adalah salah satu masalah yang kurang diperhatikan oleh masyarakat. Penelitian ini dengan metodologi penelitian observasi data sekunder dari semua literatur, termasuk jurnal, artikel dan makalah ilmiah. Berdasarkan hasil rujukan Landasan hukum pengelolaan sampah di tingkat pemerintah daerah, termasuk tanggung jawab yang dibebankan kepada masyarakat, dikendalikan oleh Peraturan Pemerintah No. 81 Tahun 2012 tentang Pengelolaan Sampah Rumah Tangga dan Sampah Sejenis Sampah Rumah Tangga, Peraturan Kepala Daerah tentang kebijakan dan strategi pengelolaan sampah rumah tangga dan sampah sejenis sampah rumah tangga, dan Instruksi Presiden No. 97 Tahun 2017 tentang kebijakan strategis pengelolaan sampah jenis ini.